How Australian construction contractors responded to the economic downturn - Zuo, Jian; Zillante, George; Xia, Bo; Chan, Albert; Zhao, Zhenyu (International Journal of Strategic Property Management, 2015)
The Global Financial Crisis (GFC) in 2008 had a significant impact on the world economy and the construction industry was no exception. This study investigates the major impacts of the 2008 GFC on the Australian construction industry and, in particular how the Australian construction contractors responded to the economic downturn. A total of 35 senior managers from the Top 100 Australian construction companies were interviewed. The findings indicate that construction companies, particularly the large ones were not affected in any significant way but are expecting some difficult financial times over the next few years and are taking actions to minimize the upcoming adverse impacts. The most common strategy adopted by Australian construction contractors is to concentrate on core business while avoiding aimless bidding. Similarly, great focus is placed on retaining human resources in order to maintain the skill set so that the company can respond quickly when market conditions improves. The research findings will provide construction contractors with insights on how to establish and sustain competitive advantages during economic slowdown and become more resilient in the future.First Publish Online: 9 Oct 2015